Staghorn Ferns at a Glance - Sydney Park Brown (EDIS)
Revised! ENH-36, a 4-page illustrated fact sheet by Sydney Park Brown, describes these popular and widely available epiphytic tropical plants native to the Philippines, including their selection, care and culture. Published by the UF Department of Environmental Horticulture, July 2007.